Programmable mobile robots as hands-on platform for basic programming (2017)
Nowadays, mobile robots platforms are being used in different education contexts. The state of the art shows that 197 papers have been published in this area knowledge over ten years. Latin America faces a problem regarding the enrolled students in engineering programs. The SPADIES program (Colombia) affirms that the lack of motivation and interaction with real artifacts relating theory and practice is an important aspect for dropout. In this work, a platform composed by a set of programmable mobile robots, and a WEB-responsive software tool for programming at different levels of knowledge were implemented. The set of mobile robots were implemented with proximity, trajectory, light, inertial, and vision sensors; also, tools such as Bluetooth and LEDs-ring are included; and, a mechanical support for an erasable marker. The WEB-responsive tool supports graphical programming for novice, Python programming for middle, and ANSI-C for advanced level learners.